“I think it's kind of sensitive in every way” : Communicating with non-Finnish-Speaking Clients in Child Welfare - Bouzaiane, Emna (2023)
Communication in Child Welfare in Finland has been researched from multiple perspectives. Some attention has also been given to how the presence of non-Finnish-speaking clients affects communication and what challenges it might add to an already sensitive and delicate field, where communication is the main tool used to assess the services clients need. Child Welfare services can be life-altering and therefore accuracy in providing services is key. However, lan-guage barriers and a lack of means to overcome these barriers render this task very difficult. This study looks at the communication between workers and non-Finnish-speaking clients at one of Finland’s around-the-clock family assessment units. The research questions for this study are how do workers at the unit experience day-to-day communication with non-Finnish-speaking clients? And how do workers at the unit experience using the assessment methods at their disposal to work with non-Finnish-speaking clients? The purpose of the study was to distinguish the experiences of Child Welfare workers when communicating with non-Finnish-speaking clients who have no to limited Finnish language proficiency during day-to-day interactions and when using the assessment methods in more structured settings. The study was also interested in exploring the different strategies workers utilized in this interaction. The aim was to investigate whether the current communication means available in Child Welfare at the disposal of the workers are sufficient to optimize and facilitate the communication between workers and non-Finnish-speaking families at the unit and in Child Welfare in general. To answer the research questions, semi-structured interviews were conducted with seven workers at the family unit. The transcripts were analyzed using Thematic Data Analysis by deducing the most reoccurring themes. Four main themes were then extracted from multiple codes covering various aspects of communication. The themes are: 1. Verbal communication, 2. Non-verbal communication, 3. Assessment methods as an effective means of communication, and 4. Participants’ attitudes. The findings revealed creativity on the part of both workers and clients to find alternative ways of achieving a common understanding and also highlighted the important role of Public Service Interpreting and the effect of its shortcomings on achieving said understanding. In addition to these, findings revealed workers’ attitudes towards working with non-Finnish-speaking clients and their developmental ideas to enhance the communication between the two parties in the future.